ANALGETIC ASSAY OF TREMBESI LEAVES (Samanea saman (Jacq.) Merr.) - KRISNA KHARISMA PERTIWI; DWI WAHYUNI; ROSA J HESTURINI; AGUSTINA DWI LESTARI (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2020)
Background: Trembesi (Samanea saman (Jacq.) Merr.) is a plant of the genus Samanea spread in tropical areainclude Indonesia. This plant have some chemical ingredients such as flavonoids, alkaloids, tannins, saponins, and steroids or triterpenoids. Objective: To know the analgesic activity and the effective dose of ethanol extract of leaves of trembesi in white male mice (Mus musculus L.). Method: This research is experimental with Post-Test Only Control Group Design techniques. Analgesic activity test was performed by chemical induction method using acetic acid in vivo with a negative control treatment (CMC-Na 0,5%), a positive control (aspirin 500mg), dose of ethanol extract of trembesi 150, 300 and 600 mg/kgBB. Data were analyzed with Hendersoth and Forsaith equation to determine the amount of stretching by mice. Analysis by One Way ANOVA test and LSD test. Results: The results showed the analgesic power percent ethanol extract of trembesi leaves are respectively 16.6%, 45.8% and 69.6%. Conclusions: The dose of ethanol extract of trembesi leaves have analgesic activity with the most effective dose is 600 mg/kgBB is equivalent to 500mg of aspirin (p=0.560).